2012
DOI: 10.1016/j.foodhyd.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α-tocopherol on physicochemical properties of chitosan-based films

Abstract: Chitosan has been exploited as a material for the development of edible films, and additionally can be used as a carrier of functional compounds such as a-tocopherol. The aim of this work was to evaluate the effects of the incorporation of a-tocopherol in chitosan-based films. FTIR and thermal analyses were performed and showed that the incorporation of a-tocopherol affects the chemical structure of chitosan-based films with the establishment of new chemical bonds and the decrease of crystallinity. Results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
222
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(257 citation statements)
references
References 53 publications
22
222
1
12
Order By: Relevance
“…A peak at 1646 cm -1 is assigned to the presence of carbonyl group (C=O) in chitosan film (Martins et al, 2012;Zemljič et al, 2013). Since the grade of chitosan used in the present study was around 80% deacetylated, the C=O stretching (amide I) peak at 1650 cm -1 and N-H bending (amide II) peak at 1580 cm -1 were observed.…”
Section: Visual Examinationmentioning
confidence: 72%
See 1 more Smart Citation
“…A peak at 1646 cm -1 is assigned to the presence of carbonyl group (C=O) in chitosan film (Martins et al, 2012;Zemljič et al, 2013). Since the grade of chitosan used in the present study was around 80% deacetylated, the C=O stretching (amide I) peak at 1650 cm -1 and N-H bending (amide II) peak at 1580 cm -1 were observed.…”
Section: Visual Examinationmentioning
confidence: 72%
“…Chitosan is a semi natural polymer obtained by deacetylation of chitin, and it has interesting properties such as excellent film forming ability and gas and aroma barrier properties at dry conditions, which makes it a suitable material in designing food coatings and packaging structures (Portes et al, 2009;Martins et al, 2012; Ruiz-Navajas et al, 2013). Pure chitosan films were described as generally cohesive, compact with smooth surface without pores or cracks (Hromiš et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When adding a-tocopherol in chitosanbased films Martins et al (2012) observed a significant decrease (p \ 0.05) in the TS was observed (from 34.06 MPa (0 %) to 16.24 MPa (0.2 %) with the increased concentration of antioxidant; however there was a similarly observed significant reduction (p \ 0.05) of EB with the addition of a-tocopherol from 53.84 % (0 %) to 23.12 % (0.2 %).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have report the development of active packaging with antioxidants incorporated to improve food preservation, such as a-tocopherol (Gomez-Estaca et al 2014;Martins et al 2012), plant extracts (Li et al 2014;Silva-Weiss et al 2013), essences oils from herbs (Salarbashi et al 2014;Silva-Weiss et al 2013), curcumin (López-de-Dicastillo et al 2012, eugenol (Burt 2004), among others. However, to date, there is limited work in the literature on the development of active films with the addition of antioxidants such as bixin.…”
Section: Introductionmentioning
confidence: 99%
“…In the UV region at 210 nm, the films showed high values, indicating a high absorption, demonstrating that these films have a high ability to protect against UV radiation, which causes the oxidative deterioration of packaged foods, leading to nutrient losses, discoloration and off-flavors [36] . This result is in agreement with previous reports on gelatinbased films [2,37] .…”
Section: Opacity Propertiesmentioning
confidence: 99%